"It went through the roof": an observation study exploring the rise in PrEP uptake among Zimbabwean female sex workers in response to adaptations during Covid‐19. (28th October 2021) - Matambanadzo, Primrose; Busza, Joanna; Mafaune, Haurovi; Chinyanganya, Lillian; Machingura, Fortunate; Ncube, Getrude; Steen, Richard; Phillips, Andrew; Cowan, Frances Mary
Abstract: Introduction: Sisters with a Voice (Sisters), a programme providing community‐led differentiated HIV prevention and treatment services, including condoms, HIV testing, pre‐exposure prophylaxis (PrEP) and antiretroviral therapy linkage for sex workers, reached over 26, 000 female sex workers (FSW) across Zimbabwe in 2020. Zimbabwe's initial Covid "lockdown" in March 2020 and associated movement restrictions interrupted clinical service provision for 6 weeks, particularly in mobile clinics, triggering the adaptation of services for the Covid‐19 context and a scale up of differentiated service delivery (DSD) models. PrEP service delivery decentralized with shifts from clinical settings towards community/home‐based, peer‐led PrEP services to expand and maintain access. We hypothesize that peer‐led community‐based provision of PrEP services influenced both demand and supply‐side determinants of PrEP uptake. We observed the effect of these adaptations on PrEP uptake among FSW accessing services in Sisters in 2020. Methods: New FSW PrEP initiations throughout 2020 were tracked by analysing routine Sisters programme data and comparing it with national PrEP initiation data for 2020. We mapped PrEP uptake among all negative FSW attending services in Sisters alongside Covid‐19 adaptations and shifts in the operating environment throughout 2020: prior to lockdown (January–March 2020), during severe restrictions (April–June 2020), subsequent easing (July–September 2020) and during drug stockouts that followed (October–December 2020). Results and discussion: PrEP uptake in 2020 occurred at rates <25% (315 initiations or fewer) per month prior to the emergence of Covid‐19. In response to Covid‐19 restrictions, DSD models were scaled up in April 2020, including peer demand creation, community‐based delivery, multi‐month dispensing and the use of virtual platforms for appointment scheduling and post‐PrEP initiation support. Beginning May 2020, PrEP uptake increased monthly, peaking at an initiation rate of 51% ( n = 1360) in September 2020. Unexpected rise in demand coincided with national commodity shortages between October and December 2020, resulting in restriction of new initiations with sites prioritizing refills. Conclusions: Despite the impact of Covid‐19 on the Sisters Programme and FSW mobility, DSD adaptations led to a large increase in PrEP initiations compared to pre‐Covid levels demonstrating that a peer‐led, community‐based PrEP service delivery model is effective and can be adopted for long‐term use.